Oxidized Monolayers of Epitaxial Silicene on Ag(111) - Johnson, Neil W. (Sci Rep, 2016)
The properties of epitaxial silicene monolayers on Ag(111) at various levels of oxidation are determined through complementary density functional theory calculations and soft X-ray spectroscopy experiments. Our calculations indicate that moderate levels of oxidation do not cause a significant bandgap opening in the epitaxial silicene monolayer, suggesting that oxygen functionalization is not a viable mechanism for bandgap tuning while the silicene monolayer remains on its metallic substrate. In addition, moderate oxidation is calculated to strongly distort the hexagonal Si lattice, causing it to cluster in regions of highest oxygen adatom concentration but retain its 2D sheet structure. However, our experiments reveal that beam-induced oxidation is consistent with the formation of islands of bulk-like SiO(2). Complete exposure of the monolayer to ambient conditions results in a fully oxidized sample that closely resembles bulk SiO(2), of which a significant portion is completely detached from the substrate.